Critical Discussion Between Islamization and Development of Science - Muhammad Subhan (Al-Hayat: Journal of Islamic Education, 2017)
The idea of Islamization of knowledge came from the anxiety of the Muslim thinkers who see the fact that almost all the forgotten history of science that most of the development of science, Islam plays an important role in the history of its development, and the state of reality that science itself has started to separate and far from Islam, departing from it all in the 1981's came around the name Islamization of science pioneered by Muhammad Naquib Al-Attas is then followed by Ismail Al-Faruqi, he suggests some prisnsip Islamization of knowledge related to this such as the rejection of any something that is not related to reality, negating the intrinsic contradictions and paradoxes protect it from unilaterally. Islamization of knowledge that is basically a scientific activity as uncover, connect and disseminate knowledge from the perspectives of the nature of human life. So Islamization of science can be regarded as an attempt liberation of the assumptions or interpretations of reality then west to replace the Islamic worldview. Islamization of science itself must have some conception of the science target pegetahuan who then proceeds to islamisas creation science. The ethics of scientific development which sometimes affects the development of science itself includes several things such as human nature, human dignity, the balance of the ecosystem, is accountable to the public interest which includes the present and future as well as universal.